The Impact of Drought and Vascular-Inhabiting Pathogen Invasion in Pinus taeda Health - Pratima Devkota; Scott A. Enebak; Lori G. Eckhardt (International Journal of Forestry Research)
The complex interaction of various biotic and abiotic factors may put the overall stand health of Pinus spp. at risk. A study was designed to determine the combined impact of drought and vascular-inhabiting fungi (Leptographium terebrantis and Grosmannia huntii) in Pinus taeda. Seedlings from two P. taeda families were planted and watering treatments, (i) normal watering, (ii) moderate drought, and (iii) severe drought, were applied. One month following the initiation of watering treatments, seedling stems were artificially inoculated with L. terebrantis and G. huntii. Drought and fungal interaction significantly affected lesion length/seedling height, occlusion length/seedling height, and seedling fine root biomass. Leptographium terebrantis was more pathogenic under moderate and severe drought than normal watering condition, whereas the pathogenicity of G. huntii remains unaltered. The susceptibility of the families to vascular-inhabiting fungi remained the same under different watering treatments. Drought and specific vascular-inhabiting fungi may negatively impact P. taeda stand health.